Trifluralin and Atrazine Sensitivity to Selected Cereal and Legume Crops - Imtiaz Faruk Chowdhury (Agronomy, 2020)
Soil-applied herbicides can persist in sufficient concentrations to affect the growth of crops in rotations. The sensitivity of wheat, barley, oat, lucerne and lentil to trifluralin and atrazine residues were investigated with three glasshouse experiments in 2018 and 2019. Each bioassay crop species was tested against different concentrations of trifluralin and atrazine in sandy soil using a full factorial design. Shoot and root parameters of the tested crop species were fitted in logistic equations against herbicide concentrations to calculate effective doses for 50% growth inhibition (ED50). Results revealed that both shoot and root parameters of all the test crop species were significantly affected by trifluralin and atrazine. Trifluralin delayed crop emergence at the lower concentrations examined, while higher concentrations prevented emergence entirely. Low concentrations of atrazine did not affect emergence but significantly reduced plant height, soil–plant analyses development (SPAD) index, shoot dry weight, root length, root dry weight and number of nodules of all the crop species. At high concentration, atrazine resulted in plant death. Legumes were found to be more sensitive than cereals when exposed to both trifluralin and atrazine treatments, with lucerne being the most sensitive to both herbicides, ED50 ranging from 0.01 to 0.07 mg/kg soil for trifluralin; and from 0.004 to 0.01 mg/kg for atrazine. Barley was the most tolerant species observed in terms of the two herbicides tested. Lucerne can be used to develop a simple but reliable bioassay technique to estimate herbicide residues in the soil so that a sound crop rotation strategy can be implemented.